ENGLISH NEOLOGISMS-ABBREVIATIONS: PECULIARITIES OF FORMATION AND SPELLING - Ivanova, N.K. (Perm Federal Research Centre Journal, 2014)
In the paper on the basis of the new words dictionaries some specific features in formation and spelling of various kinds of abbreviations (letter abbreviations, acronyms, blends, etc.) are analysed. “Abbreviation explosion”, characteristic for the current English language, is considered as the impact of the “law of efforts economy”, one of the most important in the language development. The correlation between the change in a word spelling and its pronunciation is traced, and the most typical models are established, peculiarities of upper case and lower case letters and logograms are described.